Cerium oxide particles, method for producing same, and polishing composition

By controlling the ratio and specific surface area of cerium oxide (III): (cerium oxide (IV)) of cerium oxide particles, cerium oxide particles with high silicon oxide polishing rate, low silicon nitride polishing rate and low surface defects were prepared, and the problems of low silicon oxide polishing rate and high silicon nitride polishing rate in the prior art were solved, thereby achieving an efficient selection ratio of silicon oxide to silicon nitride.

CN120288812APending Publication Date: 2025-07-11WUHAN DINGZE NEW MATERIAL TECH CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510440772.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

During the grinding process of the existing cerium oxide particles, the ratio of cerium oxide (III) and cerium oxide (IV) is improper, resulting in a low polishing rate of silicon oxide and a high polishing rate of silicon nitride, and easy to produce polishing defects.

Method used

By adding cerium carbonate to a nitric acid solution with a pH of 2-3 and adding hydrogen peroxide dropwise to a mixture of Ce(OH)3/Ce(OH)4, then calcined under a specific atmosphere, the ratio of cerium oxide (III): (cerium oxide (III) + cerium oxide (IV)) is controlled to be 40-50%, and the specific surface area is controlled to be 22-31m2/g, cerium oxide particles in a suitable proportion are prepared.

Benefits of technology

The polishing rate of silicon oxide is increased, the polishing rate of silicon nitride is reduced, the selection ratio of silicon oxide to silicon nitride is enhanced, and the surface defects are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005350992830000071
    Figure BDA0005350992830000071
  • Figure BDA0005350992830000081
    Figure BDA0005350992830000081
  • Figure BDA0005350992830000091
    Figure BDA0005350992830000091
Patent Text Reader

Abstract

The invention provides cerium oxide particles, a preparation method thereof and a composition for grinding, and relates to the technical field of nano material preparation and semiconductor polishing. The preparation method comprises the following steps: dropwise adding hydrogen peroxide with a preset proportion into a solution containing cerous carbonate, uniformly stirring, and adding the mixed solution into ammonia water to obtain Ce (OH) 3 / Ce (OH) 4 mixed precipitate; the precipitate is filtered, washed and smashed and then calcined for 2 hours in a preset atmosphere at the temperature of 750 DEG C, cerium oxide particles with the primary particle size being 30-60 nm are obtained, and the proportion range of cerium oxide (III): (cerium oxide (III) + cerium oxide (IV)) in the cerium oxide particles is 40-50%. The cerium oxide particles provided by the invention have relatively high Oxide grinding rate and relatively low OX surface defects in the grinding process, and the SiN grinding rate is kept unchanged, so that the OX / SiN selection ratio is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical fields of nanomaterial preparation and semiconductor polishing, and particularly to a cerium oxide particle, a preparation method thereof, and a polishing composition for grinding. Background Art

[0002] Chemical mechanical polishing (CMP) is one of the most effective planarization techniques in the manufacturing technologies of high-precision optical devices and ultra-large scale integrated circuits. Due to its unique chemical and physical effects, cerium oxide has a prominent selectivity ratio especially for silicon dioxide and silicon nitride films, and can accurately stop at the SiN layer while achieving a high oxide removal rate, and is widely used in the polishing process of shallow trench isolation (STI). In recent years, with the development of memory chips, there is a demand for high-efficiency oxide removal ability. Traditional polishing compositions for silicon oxide grinding are difficult to achieve this. The polishing composition using cerium oxide as an abrasive has greater application prospects and market advantages in terms of performance and cost.

[0003] In the case of using cerium oxide as an abrasive, its own particle characteristics are crucial for the polishing effect. The reason why cerium oxide can efficiently polish silicon dioxide is mainly attributed to its unique chemical mechanical polishing synergistic mechanism, that is, the synergistic effect of chemical corrosion and mechanical grinding. Due to the special electronic configuration of cerium element, cerium(III) oxide and cerium(IV) oxide in cerium oxide can be converted into each other and coexist under different conditions, making it exhibit both oxidizing and reducing properties under certain conditions. Therefore, how to provide a cerium oxide particle in which the ratio between cerium(III) oxide and cerium(IV) oxide can significantly increase the polishing rate of cerium oxide particles for silicon dioxide, while suppressing the polishing rate for silicon nitride, and without generating other polishing defects, is an urgent problem to be solved in this industry. Summary of the Invention

[0004] The present application provides a cerium oxide particle, a preparation method thereof, and a polishing composition for grinding. The preparation method prepares cerium oxide particles having a suitable ratio of cerium(III) oxide:(cerium(III) oxide + cerium(IV) oxide), so that the cerium oxide particles have a high oxide grinding rate and fewer surface defects during the grinding process, and the polishing composition has a high OX / SiN selectivity ratio.

[0005] In a first aspect, the present application provides a method for preparing cerium oxide particles, including the following steps:

[0006] S1: Add cerium carbonate to a nitric acid solution with a pH value of 2-3, then dropwise add a preset ratio of hydrogen peroxide, stir evenly, and add the mixed solution to ammonia water to obtain a precipitate, and the precipitate is a Ce(OH)3 / Ce(OH)4 mixture;

[0007] S2: Filter and wash the precipitate, crush it, and calcine it in a preset atmosphere at 750 °C for 2 hours to obtain cerium oxide particles. The primary particle size of the cerium oxide particles is 30-60 nm, and the ratio of cerium(III) to (cerium(III) + cerium(IV)) in the cerium oxide particles ranges from 40-50%.

[0008] In a possible implementation, the ratio of cerium(III) to (cerium(III) + cerium(IV)) in the cerium oxide particles ranges from 42-44%.

[0009] In a possible implementation, the specific surface area of the cerium oxide particles is 22-31 m 2 / g. Preferably, the specific surface area of the cerium oxide particles is 27-31 m 2 / g.

[0010] In a possible implementation, the preset atmosphere is a mixed gas of argon and oxygen, where the oxygen content is 5-15%.

[0011] In a possible implementation, the molar ratio of cerium carbonate to hydrogen peroxide is 1:0.5-1:3. Preferably, the molar ratio of cerium carbonate to hydrogen peroxide is 1:1-1:2.

[0012] In a possible implementation, the concentration of hydrogen peroxide is 20-40 wt%.

[0013] In a possible implementation, the dropping rate of hydrogen peroxide is 0.1-0.3 kg / min.

[0014] In a possible implementation, in step S1, the rate of adding the mixed solution to ammonia water is 0.1-0.3 kg / min, and the pH of the solution after obtaining the precipitate is greater than 10.

[0015] In the second aspect, the present application provides a cerium oxide particle, including the cerium oxide particle obtained by using the preparation method described in any one of the embodiments of the first aspect.

[0016] In the third aspect, the present application provides a polishing composition, including the cerium oxide particle described in the embodiment of the second aspect, and the polishing composition is used for the STI process.

[0017] In the above technical solution, by adding a preset proportion of hydrogen peroxide to a cerium carbonate-containing solution and then calcining the cerium hydroxide precipitate in a preset atmosphere, cerium oxide particles with a suitable cerium(III):(cerium(III)+cerium(IV)) ratio are obtained. These cerium oxide particles have a high Oxide grinding rate during the grinding process, maintain the SiN grinding rate unchanged, improve the OX / SiN selectivity, and have low OX surface defects. Detailed implementation mode

[0018] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be described clearly and completely below. For those not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. For reagents or instruments not specified by the manufacturer, they are all conventional products that can be obtained through commercial purchase.

[0019] It should be noted that the following embodiments are examples of this application, only used to illustrate this application, rather than to limit this application. Without departing from the gist or scope of this application, other combinations and various improvements within the concept of this application can be made.

[0020] The cerium oxide particles provided by this application, their preparation method, and the grinding composition will be specifically described below.

[0021] The method for preparing cerium oxide particles in the embodiments of this application includes the following steps:

[0022] S1: Add cerium carbonate to a nitric acid solution with a pH value of 2-3, then dropwise add a preset proportion of hydrogen peroxide. After stirring evenly, add the mixed solution to ammonia water to obtain a precipitate, which is a Ce(OH)3 / Ce(OH)4 mixture;

[0023] S2: Filter and wash the precipitate, crush it, and calcine it in air at 750 °C for 2 hours to obtain cerium oxide particles. The primary particle size of the cerium oxide particles is 30-60 nm, and the ratio range of cerium(III):(cerium(III)+cerium(IV)) in the cerium oxide particles is 40-50%.

[0024] The method for preparing cerium oxide particles provided by this application first adds a preset proportion of hydrogen peroxide to a solution containing cerium carbonate, adds ammonia water to obtain a Ce(OH)3 / Ce(OH)4 mixed precipitate, and then calcines the mixed precipitate under a preset atmosphere, so that the cerium oxide particles have a suitable cerium oxide (III):(cerium oxide (III)+cerium oxide (IV)) ratio. When the cerium oxide (III):(cerium oxide (III)+cerium oxide (IV)) ratio is within a suitable range, it can make the cerium oxide particles have a higher Oxide grinding rate and fewer surface defects during the grinding process, and keep the SiN grinding rate unchanged, improving the OX / SiN selectivity. In the oxidation step, by first adding hydrogen peroxide and then dropping it into ammonia water after the oxidation is completed to generate a hydroxide precipitate, the cerium ions are slowly and controllably oxidized in a weakly acidic environment, avoiding the selective oxidation of cerium ions in a basic environment and making it difficult to obtain the required oxidation ratio.

[0025] In this application, the ratio range of cerium oxide (III):(cerium oxide (III)+cerium oxide (IV)) in the precipitate is 40-50%. When the ratio of cerium oxide (III):(cerium oxide (III)+cerium oxide (IV)) in the precipitate is lower than 40%, the surface active sites of the sintered cerium oxide particles decrease. After being prepared into a grinding composition, the OX / SiN selectivity is not high, and the surface defects of OX are relatively high. When the ratio of cerium oxide (III):(cerium oxide (III)+cerium oxide (IV)) in the precipitate is higher than 50%, the OX / SiN selectivity of the sintered cerium oxide particles is not high, and the surface defects of OX are relatively high. Preferably, the ratio range of cerium oxide (III):(cerium oxide (III)+cerium oxide (IV)) in the precipitate is 42-44%. At this time, the sintered cerium oxide particles have a higher OX / SiN selectivity and lower surface defects after being prepared into a grinding composition.

[0026] In this application, the specific surface area of the cerium oxide particles is 22-31m 2 / g. The larger the specific surface area, the more active sites on the surface of the cerium oxide particles, the faster the chemical reaction rate with the material to be polished. Moreover, the cerium oxide particles can be more evenly distributed on the surface of the polishing pad, increasing the contact area with the material, reducing scratches and improving the mechanical removal efficiency. However, when the specific surface area is too high, the suspension stability of the cerium oxide particles decreases, and too many active sites may lead to local over-corrosion and an increase in surface defects. Preferably, the specific surface area of the cerium oxide particles is 27-31m 2 / g. The cerium oxide within this range has suitable surface active sites, can achieve a higher OX / SiN selectivity, and the surface defects of OX are also relatively low.

[0027] In this application, the preset atmosphere in step S2 is a mixed gas of argon and oxygen, where the oxygen content is 5-15%. When sintering cerium oxide particles using this preset atmosphere, the proportion of cerium(III) oxide in the finally obtained cerium oxide particles can be made more appropriate. When sintering with air or other gases, if the oxygen content in the sintering atmosphere is too high or too low, the oxygen vacancy concentration will be too low or too high. Therefore, the ratio of cerium(III) oxide:(cerium(III) oxide + cerium(IV) oxide) and the specific surface area of the obtained cerium oxide particles are outside the appropriate range, affecting the grinding effect of the cerium oxide particles.

[0028] In this application, the molar ratio of cerium carbonate to hydrogen peroxide is 1:0.5-1:3, so as to obtain a preset ratio of cerium(III) oxide:(cerium(III) oxide + cerium(IV) oxide). On the one hand, it enables the prepared cerium oxide particles to have a higher Oxide grinding rate and fewer surface defects during the grinding process; on the other hand, it saves the amount of hydrogen peroxide used in the preparation process, which is beneficial to reducing the preparation cost. Preferably, the molar ratio of cerium carbonate to hydrogen peroxide is 1:1-1:2. At this ratio, the proportion of cerium(III) oxide in the prepared cerium oxide is more appropriate, enabling the cerium oxide particles to have a high OX / SiN selectivity ratio and low OX surface defects after being prepared into a grinding composition.

[0029] In this application, the concentration of hydrogen peroxide is 20-40 wt%. When the concentration of hydrogen peroxide is too low, the oxidation ability is weak. Although it is easy to control the oxidation degree of cerium ions, a greater time cost is required in the oxidation step. When the concentration of hydrogen peroxide is too high, the oxidation ability is strong, and it is difficult to control the oxidation degree of cerium ions.

[0030] In this application, the dropping rate of hydrogen peroxide is 0.1-0.3 kg / min. It can be understood that when the dropping rate is relatively slow, the instantaneous oxidant concentration is small, the oxidation ability is weak, and it is easy to control the oxidation degree of cerium ions. When the dropping rate is relatively fast, the instantaneous oxidant concentration is large, the oxidation ability is strong, and it is difficult to control the oxidation degree of cerium ions.

[0031] In this application, in step S1, the rate of adding the mixed solution to ammonia water is 0.1-0.3 kg / min, and the pH of the solution after precipitation is greater than 10. By controlling the rate of adding the mixed solution to ammonia water, cerium ions can be fully precipitated; the pH of the solution after precipitation is greater than 10, that is, the ammonia water content is excessive, so that all cerium ions are precipitated as cerium hydroxide.

[0032] In this application, in step S2, the precipitate is washed until the conductivity σ < 1 mS / cm. A low conductivity means that the ion concentration in the solution is low, which is beneficial to removing impurities in the precipitate and enabling the cerium oxide particles to meet the requirements in the CMP process.

[0033] In this application, in step S2, the D50 particle size after precipitation and pulverization is 20 - 30 μm. By controlling the D50 particle size of the powder before sintering to be 20 - 30 μm, it is beneficial to reduce the dispersion difficulty and at the same time control the cerium oxide particles after sintering to have high mechanical strength.

[0034] The cerium oxide particles provided by this application can be applied in a polishing composition. This application also provides a polishing composition, including water and the cerium oxide particles of any one of the above implementation manners. The ratio of cerium(III) in the cerium oxide particles: (cerium(III) + cerium(IV)) is 40 - 50%, and the specific surface area of the cerium oxide particles is 22 - 31 m 2 / g. It has a high Oxide polishing rate and fewer surface defects during the polishing process, and can achieve a higher OX / SiN selectivity ratio.

[0035] The water is preferably deionized water.

[0036] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0037] Example 1

[0038] S1: Load 2 kg of cerium carbonate into a glass reaction kettle, add 5 kg of nitric acid solution with pH = 2, stir for 10 minutes after dissolution, and then drop 30% H2O2 at a rate of 0.2 kg / min. The molar ratio of cerium carbonate to hydrogen peroxide is 1:0.5. The clear cerium carbonate aqueous solution gradually turns orange and flocculent substances are generated. After dropping, continue to stir for 30 minutes to obtain solution A; Prepare another glass reaction kettle filled with 5 kg of ultrapure water, inject 1.3 kg of about 28 wt% ammonia water into it, and stir for 10 minutes to obtain solution B; Under well-ventilated conditions, to maintain an alkaline environment, pump solution A into solution B at a rate of 0.2 kg / min. Orange precipitates gradually precipitate out. This precipitate is a Ce(OH)3 / Ce(OH)4 mixture, and at this time the pH is greater than 10.

[0039] S2: Subsequently, the precipitate is filtered and washed with water until the conductivity σ < 1 mS / cm. After centrifuging to remove excess water, it is dried under reduced pressure for 12 h to obtain the dried crude Ce(OH)3 / Ce(OH)4 material. It is pulverized to a D50 particle size of 20 - 30 μm at a power of 12 Hz using a high-pressure air pulverizer (MSK-SFM-AF100), and the pulverized material is the raw material to be calcined. The Ce(OH)3 / Ce(OH)4 powder is loaded into an alumina crucible and calcined in a mixed gas of Ar:O2 = 95:5 at 750 °C for 2 hours to obtain approximately 1.6 kg of yellowish-white powder. XRD is used to confirm that this powder is cerium oxide, with an initial primary particle size of 30 - 60 nm, and the particle size distribution is measured by Malvern Mastersizer3000+. The morphology of the calcined material is observed by SEM to be in a fragmented block shape, and the SEM is taken using a Thermo Fisher field emission Apreo SEM series electron microscope.

[0040] Example 2

[0041] Except that the molar ratio of cerium carbonate to hydrogen peroxide in step S1 is changed from 1:0.5 to 1:1, the reaction is carried out in the same manner as the method described in Example 1 above.

[0042] Example 3

[0043] The molar ratio of cerium carbonate to hydrogen peroxide in step S1 is changed from 1:0.5 to 1:1, and the mixed gas of Ar:O2 = 95:5 in step S2 is changed to Ar:O2 = 90:10. The reaction is carried out in the same manner as the method described in Example 1 above.

[0044] Example 4

[0045] The molar ratio of cerium carbonate to hydrogen peroxide in step S1 is changed from 1:0.5 to 1:1.5, and the mixed gas of Ar:O2 = 95:5 in step S2 is changed to Ar:O2 = 85:15. The reaction is carried out in the same manner as the method described in Example 1 above.

[0046] Example 5

[0047] The molar ratio of cerium carbonate to hydrogen peroxide in step S1 is changed from 1:0.5 to 1:2, and the mixed gas of Ar:O2 = 95:5 in step S2 is changed to Ar:O2 = 85:15. The reaction is carried out in the same manner as the method described in Example 1 above.

[0048] Example 6

[0049] In step S1, change the molar ratio of cerium carbonate to hydrogen peroxide from 1:0.5 to 1:3, and in step S2, change the mixed gas of Ar:O2 = 95:5 to Ar:O2 = 82:18. React in the same manner as the method described in Example 1 above.

[0050] Comparative Example 1

[0051] Except for changing the molar ratio of cerium carbonate to hydrogen peroxide in step S1 from 1:0.5 to 1:0.3, react in the same manner as the method described in Example 1 above.

[0052] Comparative Example 2

[0053] Except for changing the molar ratio of cerium carbonate to hydrogen peroxide in step S1 from 1:0.5 to 1:5, react in the same manner as the method described in Example 1 above.

[0054] Comparative Example 3

[0055] Load 2 kg of cerium carbonate into an alumina crucible and directly calcine it in air at 800 °C for 2 hours to obtain about 1.8 kg of a yellowish-white powder. Use XRD to confirm that the powder is cerium oxide, with an initial primary particle size of 30 - 50 nm. Observe the morphology of the calcined material by SEM as fragmented blocks.

[0056] Comparative Example 4

[0057] Change step S1 to "Add a mixed solution of hydrogen peroxide and ammonia water in a preset ratio dropwise to the cerium carbonate solution", and react in the same manner as the method described in Example 1 above.

[0058] Comparative Example 5

[0059] Change step S1 to "Add hydrogen peroxide in a preset ratio dropwise to the cerium carbonate solution, stir evenly, and then add ammonia water dropwise to the mixed solution", and react in the same manner as the method described in Example 1 above.

[0060] Comparative Example 6

[0061] In step S1, change the molar ratio of cerium carbonate to hydrogen peroxide from 1:0.5 to 1:1, and in step S2, change the mixed gas of Ar:O2 = 95:5 to air. React in the same manner as the method described in Example 1 above.

[0062] Comparative Example 7

[0063] In step S1, change the molar ratio of cerium carbonate to hydrogen peroxide from 1:0.5 to 1:1, and in step S2, change the mixed gas of Ar:O2 = 95:5 to nitrogen. React in the same manner as the method described in Example 1 above.

[0064] Comparative Example 8

[0065] In Step S1, change the molar ratio of cerium carbonate to hydrogen peroxide from 1:0.5 to 1:1, and in Step S2, change the mixed gas of Ar:O2 = 95:5 to Ar:O2 = 60:40, and perform the reaction in the same manner as the method described in Example 1 above.

[0066] Comparative Example 9

[0067] In Step S1, change the molar ratio of cerium carbonate to hydrogen peroxide from 1:0.5 to 1:1, and in Step S2, change the mixed gas of Ar:O2 = 95:5 to Ar:O2 = 97:3, and perform the reaction in the same manner as the method described in Example 1 above.

[0068] In the examples and comparative examples, the physical properties of the cerium oxide particles were measured according to the following method.

[0069] (1) The actual valence state ratio of cerium oxide particles in the polishing liquid was determined by X-ray photoelectron spectroscopy (XPS). According to the different peak positions and peak shapes of different valence states in CeO2 under X-ray irradiation, the ratio of cerium(III) / cerium(IV) oxide was determined. XPS was performed using a Shimadzu AXIS SUPRA X-ray photoelectron spectrometer;

[0070] (2) The specific surface area of the cerium oxide particles was measured by a Micromeritics ASAP 2460 automatic physical adsorption analyzer (BET).

[0071] Table 1 Physical property measurement results of Examples 1-6 and Comparative Examples 1-9

[0072]

[0073]

[0074] As can be seen from Table 1 and Examples 1-6, when the molar ratio of cerium carbonate to hydrogen peroxide is 1:0.5 - 1:3, and the preset atmosphere is a mixed gas of argon and oxygen with an oxygen content of 5 - 15%, cerium oxide particles with a ratio of cerium(III):(cerium(III) + cerium(IV)) and a specific surface area within suitable ranges can be prepared.

[0075] By comparing Examples 1, 2, 6 and Comparative Examples 1-2, it can be seen that when the molar ratio of cerium carbonate to hydrogen peroxide is 1:0.5 - 1:3, the ratio range of cerium(III):(cerium(III) + cerium(IV)) is 40 - 50%, and the specific surface area of the cerium oxide particles is 22 - 31 m 2within the range of / g. When the hydrogen peroxide content is low, the cerium(III) oxide content is low, and the specific surface area of the cerium oxide particles is small; when the hydrogen peroxide content is excessive, the cerium(III) oxide content is high, and the specific surface area of the cerium oxide particles is too large.

[0076] By comparing Example 2 with Comparative Examples 3-5, it can be seen that in the oxidation step of the present application, by first adding hydrogen peroxide and then dropping it into ammonia water after oxidation is completed to form a hydroxide precipitate, the cerium ions are slowly and controllably oxidized in a weakly acidic environment, so as to obtain cerium oxide particles with both the ratio of cerium(III) oxide:(cerium(III) oxide + cerium(IV) oxide) and the specific surface area within a suitable range. If cerium carbonate is directly calcined, the cerium(III) oxide content in the obtained cerium oxide particles is low, and the specific surface area of the cerium oxide particles is small. If a mixed solution of hydrogen peroxide and ammonia water is added dropwise at the same time, the specific surface area of the obtained cerium oxide particles is moderate, but the cerium(III) oxide content is low. If ammonia water is added dropwise to the mixed solution after adding hydrogen peroxide, cerium oxide particles with too large a specific surface area will be obtained.

[0077] By comparing Examples 2-5 with Comparative Examples 6-9, it can be seen that the preset atmosphere of the present application is a mixed gas of argon and oxygen, and the oxygen content is 5-15%. The cerium oxide particles sintered in this environment have a suitable ratio of cerium(III) oxide:(cerium(III) oxide + cerium(IV) oxide) and specific surface area. When the preset gas is air, the cerium(III) oxide content in the sintered cerium oxide particles is too low; when the preset gas is nitrogen, the cerium(III) oxide content in the sintered cerium oxide particles is high, but the specific surface area is too high. When the oxygen content in the mixed gas of argon and oxygen is too high, the cerium(III) oxide content in the sintered cerium oxide particles is too low; when the oxygen content in the mixed gas of argon and oxygen is too low, the cerium(III) oxide content in the sintered cerium oxide particles is too high.

[0078] Configuration of the grinding composition

[0079] The above-mentioned cerium oxide powder is made into a 15% aqueous solution, wet-ground (Hosokawa Micron AHM series) with zirconia beads for 2 hours to obtain a slurry with a particle size distribution of D90 less than 800 nm, and then centrifugally classified at different speeds to D50 of about 150 nm. The DLS particle size measured by a Malvern particle size analyzer is 115 nm. 1 kg of the slurries prepared from the cerium oxide powders of Examples 1-3 and Comparative Examples 1-4 according to the above process are respectively mixed with 78 g of an aqueous polyacrylic acid solution (30 wt%) and 9922 g of ultrapure water, and after ultrasonic stirring for 10 min, a 2 wt% finished polishing liquid with a pH of 4.8 is obtained through a 1.0 / 0.5 μm filter membrane.

[0080] Polishing Experiment: The polishing composition is used to polish the silicon dioxide layer. 300 mL / min of the above cerium oxide polishing liquid is dripped onto the platform on the Reflexion LK machine, and at the same time, the platform / rotating head rotates at 113 / 107 rpm respectively. After 30 s under the main polishing pressure of 2 psi, the surface of the wafer is cleaned with ultrapure water and ammonia water, and the moisture on the surface of the wafer is spun dry by spin drying. The film thickness change of the wafer surface before and after measurement is carried out by using an optical ellipsometer, and the surface defects are measured by using SP2. By measuring the mass difference before and after polishing, the thickness is calculated as the polishing rate, and the results are listed in Table 2.

[0081] Table 2 Polishing Results of Examples 1-6 and Comparative Examples 1-9

[0082]

[0083]

[0084] As can be seen from Table 2 and Examples 1-6, when the molar ratio of cerium carbonate to hydrogen peroxide is 1:0.5 - 1:3, and the preset atmosphere is a mixed gas of argon and oxygen with an oxygen content of 5 - 15%, the prepared cerium oxide particles have a high OX polishing rate and low OX surface defects, and the SiN polishing rate remains low, improving the OX / SiN selectivity. Among them, the OX / SiN selectivity of Examples 2-5 is greater than 200, and the number of OX surface defects is less than 30. Example 2 has the best polishing effect.

[0085] By comparing Examples 1, 2, 6 and Comparative Examples 1-2, it can be seen that when the molar ratio of cerium carbonate to hydrogen peroxide is 1:0.5 - 1:3, the prepared cerium oxide particles have a high OX polishing rate and low OX surface defects, the SiN polishing rate remains low, and the OX / SiN selectivity is improved. When the content of hydrogen peroxide is too little or too much, the OX polishing rate of the cerium oxide particles is low, the SiN polishing rate hardly changes, the OX / SiN selectivity is small, and the number of OX surface defects increases.

[0086] By comparing Example 2 with Comparative Examples 3-5, it can be seen that in the oxidation step of the present application, by first adding hydrogen peroxide and then dropping it into ammonia water after the oxidation is completed to form a hydroxide precipitate, the cerium ions are slowly and controllably oxidized in a weakly acidic environment. The obtained cerium oxide particles have a high OX grinding rate, a relatively high OX / SiN selectivity, and fewer surface defects on OX. If cerium carbonate is directly calcined, the obtained cerium oxide particles have a high OX grinding rate and a high SiN grinding rate, resulting in a relatively small OX / SiN selectivity and more surface defects on OX. If a mixed solution of hydrogen peroxide and ammonia water is dropped simultaneously, the obtained cerium oxide particles have a moderate OX / SiN selectivity, but more surface defects on OX. If ammonia water is dropped into the mixed solution after adding hydrogen peroxide, the obtained cerium oxide particles have both a low OX grinding rate and a low SiN grinding rate, a moderate OX / SiN selectivity, but more surface defects on OX.

[0087] By comparing Examples 2-5 with Comparative Examples 6-9, it can be seen that the preset atmosphere of the present application is a mixed gas of argon and oxygen, and the oxygen content is 5-15%. The cerium oxide particles sintered in this environment have a high OX grinding rate and low surface defects on OX, and the SiN grinding rate remains low, improving the OX / SiN selectivity. When the preset gas is air, the OX grinding rate and SiN grinding rate of the sintered cerium oxide particles are both low, the OX / SiN selectivity is relatively small, and there are more surface defects on OX; when the preset gas is nitrogen, the OX grinding rate and SiN grinding rate of the sintered cerium oxide particles are both moderate, the OX / SiN selectivity is relatively small, and there are more surface defects on OX. When the oxygen content in the mixed gas of argon and oxygen is too high, the OX grinding rate of the sintered cerium oxide particles is low, the OX / SiN selectivity is relatively small, and there are more surface defects on OX; when the oxygen content in the mixed gas of argon and oxygen is too low, the OX grinding rate of the sintered cerium oxide particles is moderate, the SiN grinding rate is low, the OX / SiN selectivity is moderate, but there are more surface defects on OX.

[0088] Although the embodiments of the present application have been disclosed as above, they are not limited to the applications listed in the specification and embodiments. It can be fully applied to various fields suitable for the present application. For those familiar with the field, additional modifications can be easily made. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present application is not limited to the specific details and the embodiments shown and described here.

Claims

1. A method for preparing cerium oxide particles, characterized in that, It includes the following steps: S1: Add cerium carbonate to a nitric acid solution with a pH value of 2 - 3, then dropwise add hydrogen peroxide in a preset ratio. After stirring evenly, add the mixed solution to ammonia water to obtain a precipitate, and the precipitate is a Ce(OH)3 / Ce(OH)4 mixture; S2: Filter and wash the precipitate, crush it, and calcine it in a preset atmosphere at 750 °C for 2 hours to obtain cerium oxide particles. The primary particle size of the cerium oxide particles is 30 - 60 nm, and the ratio of cerium(III) oxide in the cerium oxide particles: (cerium(III) oxide + cerium(IV) oxide) ranges from 40 - 50%.

2. The method for preparing cerium oxide particles according to claim 1, wherein The ratio of cerium(III) oxide in the cerium oxide particles: (cerium(III) oxide + cerium(IV) oxide) ranges from 42 - 44%.

3. The method for preparing cerium oxide particles according to claim 1, wherein The specific surface area of the cerium oxide particles is 22-31 m 2 / g.

4. The method for preparing cerium oxide particles according to any one of claims 1-3, characterized in that, The preset atmosphere is a mixed gas of argon and oxygen, wherein the oxygen content is 5 - 15%.

5. The method for preparing cerium oxide particles according to any one of claims 1-3, characterized in that, The molar ratio of cerium carbonate to hydrogen peroxide is 1:0.5 - 1:

3.

6. The method for preparing cerium oxide particles according to claim 5, wherein, The concentration of hydrogen peroxide is 20 - 40 wt%.

7. The method for preparing cerium oxide particles according to claim 5, characterized in that, The dropping rate of hydrogen peroxide is 0.1 - 0.3 kg / min.

8. The method for preparing cerium oxide particles according to any one of claims 1-3, characterized in that, In step S1, the rate at which the mixed solution is added to ammonia water is 0.1 - 0.3 kg / min, and the pH of the solution after obtaining the precipitate is greater than 10.

9. A cerium oxide particle, characterized in that, It includes cerium oxide particles obtained by using the preparation method described in any one of claims 1 - 8.

10. A composition for grinding, characterized in that, It includes the cerium oxide particles described in claim 9, and the grinding composition is used for the STI process.